Complete response of metastatic renal cancer with dendritic cell vaccine - Dall'Oglio,Marcos (2003)
INTRODUCTION: We report a case of metastatic renal cell carcinoma that presented involution following therapy with dendritic cells. CASE REPORT: Male, 51-year old patient underwent left radical nephrectomy in September 1999 due to renal cell carcinoma, evolved with recurrence of the neoplasia in January 2002, confirmed by resection of the lesion. A vaccine therapy based on dendritic cells was then performed during 5 months (4 applications). After this period, there was occurrence of new lesions, whose resection revealed areas of necrosis and inflammatory infiltrate. DISCUSSION: The outcome of renal cell carcinoma is influenced by prognostic factors that confer more aggressive tumor characteristics. However, in cases of recurrence, the systemic therapy with dendritic cells-based vaccine can be associated with a better outcome with regression of disease.